Biofilm production and its effects on virulence of MRSA: a study in tertiary care hospital, Delhi - Khan, Amir; Tewari, Rachna; ., Neetusree; Dudeja, Mridu (International Journal Of Community Medicine And Public Health, 2020)
Background: The aim of this study was to study the prevalence of biofilm formation in MRSA and its effect on virulence and the antimicrobial resistance pattern on MRSA strains from different clinical samples. Methods: A total of 221 isolates of S. aureus isolates were selected from various clinical specimens. Prevalence was estimated according to age, sex, and location. The antibiotic susceptibility test was conducted according to the guidelines of CLSI by the VITEK 2 automated system. 113 strains were identified as MRSA by cefoxitin disc methods which were then subjected to Microtiter plate assay method to confirm phenotypic biofilm formation. Results: 51.13% isolates were resistant to methicillin, and 48.86% isolates were methicillin sensitive. The most common source of MRSA isolation was blood. MRSA isolates were mostly isolated from male. 33.63% MRSA and 19.44% MSSA isolates were strong biofilm producers while 12.38% MRSA and 14.81% were low biofilm producers. The resistance for commonly used antibiotics like benzyle penicillin, ciprofloxacin, cotrimoxazole, and erythromycin was more in MRSA strains and MIC was higher in biofilm producers. Conclusion: Statistical difference was observed between MSSA and MRSA regarding biofilm formation and antimicrobial resistance. A Biofilm producer shows resistance to many antibiotics and also make host immunity in effective. In hospitals Biofilm production should be checked regularly before giving treatment. And research should be done to find out other effective drugs to eradicate biofilms.